2006
DOI: 10.1523/jneurosci.5055-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Connexin29 Is Highly Expressed in Cochlear Schwann Cells, and It Is Required for the Normal Development and Function of the Auditory Nerve of Mice

Abstract: Connexins (Cxs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 42 publications
(60 reference statements)
3
61
0
Order By: Relevance
“…MAG is a member of the CNS-derived myelin-based growth inhibitors that also include Nogo and OmgP ( oligodendrocyte myelin glycoprotein). MAG is strongly expressed in the axonal myelin of SG of adult [Martini, 1994] and newborn mice [Tang et al, 2006]. RhoA seems to be a mediator in activation of myelin-based growth inhibitors while p75 NTR -/-can direct RhoA [Yamashita et al, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…MAG is a member of the CNS-derived myelin-based growth inhibitors that also include Nogo and OmgP ( oligodendrocyte myelin glycoprotein). MAG is strongly expressed in the axonal myelin of SG of adult [Martini, 1994] and newborn mice [Tang et al, 2006]. RhoA seems to be a mediator in activation of myelin-based growth inhibitors while p75 NTR -/-can direct RhoA [Yamashita et al, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…A newly discovered member of the Cx gene family, Cx29, has been found to be expressed in the cochlea [Ahmad et al, 2003;Yang et al, 2005;Tang et al, 2006]. At least 3 heterozygous mutations (c.807A ] T, c.781 + 10C ] G and c.781 + 15C ] T) and 2 heterozygous polymorphisms (781 + 62G ] A and c. * +2 T ] G) of the Cx29 gene have been reported in nonsyndromic deafness patients from Taiwan .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have also indicated that Cx29 protein is expressed in the mouse or rat cochlea, including in the cochlea neurons, spiral limbus, spiral ligament, organ of Corti, stria vascularis, Schwann cells myelinating the soma and the fiber of spiral ganglion neurons [Yang et al, 2005;Tang et al, 2006]. The Cx29 gene (NM 181538), which contains 2 exons and an open reading frame of 840 base pairs, is localized on chromosome 7q22.1.…”
Section: Introductionmentioning
confidence: 99%
“…However, Cx29 does not accumulate in gap junctional plaques in vivo in oligodendrocytes or Schwann cells (Altevogt et al 2002;Nagy et al 2003;Altevogt and Paul 2004) or form function gap junctions when expressed in tissue culture cells (Altevogt et al 2002). On the other hand, the Cx29 KO does show a myelin defect but one that is restricted to cell bodies of the spiral ganglion neurons in the organ of Corti (Tang et al 2006). …”
Section: Gap Junctions In Myelin and The Central Nervous Systemmentioning
confidence: 99%